Electrochemical Energy Storage Devices
Patent Information
- Application Number
- JP2023007216
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2016-05-27
- Filing Date
- 2023-01-20
- Publication Date
- 2025-03-03
- Estimated Expiration
- 2037-04-27
Smart Images

Figure 0007638008000010 
Figure 0007638008000011 
Figure 0007638008000012
Abstract
Description
[Technical field]
[0001] (CROSS REFERENCE TO RELATED APPLICATIONS) This patent application claims priority to and the benefit of U.S. Provisional Patent Application No. 62 / 342,838, entitled "NOVEL ELECTROCHEMICAL ENERGY STORAGE DEVICE," filed May 27, 2016. The entire contents of the above-mentioned patent application are incorporated by reference as part of the disclosure of this patent document. (STATEMENT REGARDING FEDERALLY SPONSORED RESEARCH OR DEVELOPMENT)
[0002] This invention was made with Government support under Grant No. DE-AR0000646 awarded by the Department of Energy's Advanced Research Projections Agency-Energy (ARPA-E). The Government has certain rights in this invention. Summary of the Invention [Means for solving the problem]
[0003] In an exemplary embodiment, an electrochemical device is disclosed that includes an ionically conductive electrolyte that includes a solution of one or more salts and one or more compressed gas solvents, each compressed gas solvent being in one of a liquid-only phase and a combination of gas and liquid phases, the one or more compressed gas solvent solutions having a vapor pressure greater than atmospheric pressure at room temperature; a housing configured to encase the ionically conductive electrolyte and provide a pressurized condition for the one or more salts and one or more compressed gas solvent solutions; and a pair of electrodes in contact with the ionically conductive electrolyte.
[0004] In an exemplary electrochemical device, the compressed gas solvent includes one or more of fluoromethane, difluoromethane, fluoroethane, difluoromethane, chloromethane, chloroethane, carbon dioxide, tetrafluoroethane, difluoroethane, and difluorochloromethane.
[0005] In an exemplary electrochemical device, the one or more salts include one or more of lithium bis(trifluoromethanesulfonyl)imide, lithium hexafluorophosphate, lithium perchlorate, lithium tetrachloroaluminate, lithium tetragallium aluminate, lithium bis(fluorosulfonyl)imide, lithium aluminum fluoride, lithium hexafluoroarsenate, lithium chloroaluminate, lithium chlorotitanate, lithium hexafluorotitanate, lithium tetrabromoaluminate, lithium tetrachloroborate, lithium tetrafluoroborate, lithium tetrachloroaluminate, sodium hexafluorophosphate, and magnesium hexafluorophosphate.
[0006] In an exemplary embodiment, the electrochemical device further comprises an additional gaseous electrolyte comprising one or more of sulfur dioxide, carbon disulfide, oxygen, nitrogen, and ammonia.
[0007] In an exemplary electrochemical device, at least one of the electrode pairs is composed of any one of lithium, sodium, magnesium, potassium, sulfur, and oxygen.
[0008] In another illustrative embodiment, an electrochemical device includes an ionically conductive catholyte comprising a solution of one or more salts and one or more compressed gas catholyte, each compressed gas catholyte being in one of a liquid-only phase and one of a combination of gas and liquid phases, wherein the one or more compressed gas catholyte solutions have a vapor pressure greater than atmospheric pressure at room temperature; a housing configured to encase the ionically conductive catholyte and provide a pressurized condition for the one or more salts and one or more compressed gas catholyte solutions; and an anode electrode and a cathode current collector in contact with the ionically conductive catholyte.
[0009] In an exemplary electrochemical device, the compressed gas catholyte includes one or more of thionyl fluoride, thionyl fluoride chloride, phosphoryl fluoride, phosphoryl fluoride chloride, sulfuryl fluoride, and sulfuryl fluoride chloride.
[0010] In an exemplary electrochemical device, the one or more salts include one or more of lithium bis(trifluoromethanesulfonyl)imide, lithium hexafluorophosphate, lithium perchlorate, lithium tetrachloroaluminate, lithium tetragallium aluminate, lithium bis(fluorosulfonyl)imide, lithium aluminum fluoride, lithium hexafluoroarsenate, lithium chloroaluminate, lithium chlorotitanate, lithium hexafluorotitanate, lithium tetrabromoaluminate, lithium tetrachloroborate, lithium tetrafluoroborate, lithium tetrachloroaluminate, sodium hexafluorophosphate, and magnesium hexafluorophosphate.
[0011] In an exemplary embodiment, the electrochemical device further comprises an additive comprising one or more of lithium chloride, lithium fluoride, sodium fluoride, sodium chloride, bromine monochloride, bromine monofluoride, chloride, and fluoride.
[0012] In an exemplary electrochemical device, the anode is composed of one or more of lithium, sodium, calcium, magnesium, aluminum, iron, zinc, cadmium, and lead.
[0013] In an exemplary electrochemical device, the cathode current collector is composed of one or more of activated carbon, carbon black, and carbon nanotubes.
[0014] An exemplary method of making a liquefied gas electrolyte solution is also disclosed, which includes loading a predetermined weight of salt into a cell, the predetermined weight of salt depending on a concentration of the salt and a volume of compressed gas solvent, cooling the cell to a first temperature lower than a second temperature of a source of the compressed gas solvent, evaporating a controlled amount of the compressed gas solvent from the source, condensing the compressed gas solvent within the cell, and sealing the cell.
[0015] In an exemplary method of making a liquefied gas electrolyte solution, the condensing operation is performed through tubing connected to the cell using one of a mass flow controller and a mass flow meter.
[0016] In an exemplary method of making a liquefied gas electrolyte solution, the sealing operation is performed using one of a valve, a plug, and a welded cover. (Background technology)
[0017] This patent application relates to electrochemical materials and electrochemical energy storage devices. [Brief description of the drawings]
[0018] [Figure 1] FIG. 1 shows exemplary optical images of lithium metal immersed for 5 days in fluoromethane containing various electrolyte additive components at small weight percentages.
[0019] [Diagram 2] FIG. 2 shows exemplary electrochemical performance of a lithium cobalt oxide (LiCoO) cathode with a lithium metal anode and an electrolyte composed of 0.2 molar (M) lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) in a 9:1 weight ratio of fluoromethane:carbon dioxide.
[0020] [Diagram 3]FIG. 3 shows an exemplary lithium|lithium symmetric cell containing 0.2 M lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) salt in 19:1 fluoromethane:CO solvent cycled at 1 mA / cm current density.
[0021] [Figure 4] FIG. 4 shows the increase in conductivity of an exemplary electrolyte due to an increase in cell pressure.
[0022] [Diagram 5] FIG. 5 illustrates an exemplary electrochemical device.
[0023] [Figure 6] FIG. 6 illustrates another exemplary electrochemical device.
[0024] [Figure 7] FIG. 7 shows the electrochemical impedance spectrum of a lithium metal LiCoO2 cell.
[0025] [Figure 8A] FIG. 8A shows the physical and chemical properties of liquefied gas solvents. [Figure 8B] FIG. 8B shows the physical and chemical properties of liquefied gas solvents. [Figure 8C] FIG. 8C shows the physical and chemical properties of liquefied gas solvents. [Figure 8D] FIG. 8D shows the physical and chemical properties of liquefied gas solvents.
[0026] [Figure 9A] FIG. 9A shows the electrolytic conductivity of the liquefied gas electrolyte over temperature. [Figure 9B] FIG. 9B shows the electrolytic conductivity of the liquefied gas electrolyte over temperature. [Figure 9C] FIG. 9C shows the electrolytic conductivity of the liquefied gas electrolyte over temperature. [Figure 9D] FIG. 9D shows the electrolytic conductivity of the liquefied gas electrolyte over temperature.
[0027] [Figure 10A] FIG. 10A shows the electrochemical stability of difluoromethane and its use in electrochemical capacitors. [Figure 10B] FIG. 10B shows the electrochemical stability of difluoromethane and its use in electrochemical capacitors. [Figure 10C] FIG. 10C shows the electrochemical stability of difluoromethane and its use in an electrochemical capacitor.
[0028] [Figure 11A] FIG. 11A shows the electrochemical stability of fluoromethane and carbon dioxide and their use in lithium batteries. [Figure 11B] FIG. 11B shows the electrochemical stability of fluoromethane and carbon dioxide and their use in lithium batteries. [Figure 11C] FIG. 11C shows the electrochemical stability of fluoromethane and carbon dioxide and their use in lithium batteries. [Figure 11D] FIG. 11D shows the electrochemical stability of fluoromethane and carbon dioxide and their use in lithium batteries. [Figure 11E] FIG. 11E shows the electrochemical stability of fluoromethane and carbon dioxide and their use in lithium batteries. [Figure 11F] FIG. 11F shows the electrochemical stability of fluoromethane and carbon dioxide and their use in lithium batteries.
[0029] [Figure 12](FIG. 12A) FIG. 12A shows the XPS spectrum of the lithium metal surface product and the calculated composition % ratio. (FIG. 12B) FIG. 12B shows the XPS spectrum of the lithium metal surface product and the calculated composition % ratio. (FIG. 12C) FIG. 12C shows the XPS spectrum of the lithium metal surface product and the calculated composition % ratio. (FIG. 12D) FIG. 12D shows the XPS spectrum of the lithium metal surface product and the calculated composition % ratio. (FIG. 12E) FIG. 12E shows the XPS spectrum of the lithium metal surface product and the calculated composition % ratio.
[0030] [Figure 13] (FIG. 13A) FIG. 13A shows the XPS spectrum of the LiCoO2 electrode and the calculated composition percentage. (FIG. 13B) FIG. 13B shows the XPS spectrum of the LiCoO2 electrode and the calculated composition percentage. (FIG. 13C) FIG. 13C shows the XPS spectrum of the LiCoO2 electrode and the calculated composition percentage.
[0031] [Figure 14] FIG. 14 shows the ionization potentials and electron affinities of liquefied gas solvents.
[0032] [Figure 15] FIG. 15 shows the viscosity of liquefied gas solvents.
[0033] [Figure 16] FIG. 16 shows the electrolytic conductivity of difluoromethane-based electrolytes.
[0034] [Figure 17] FIG. 17 shows the performance of the electrochemical capacitor.
[0035] [Figure 18] FIG. 18 shows an optical image of lithium metal after immersion in a liquefied gas solvent.
[0036] [Figure 19]FIG. 19 shows the XRD spectrum of lithium metal after immersion in a liquefied gas solvent.
[0037] [Figure 20] FIG. 20 shows the FTIR spectrum of lithium metal after immersion in a liquefied gas solvent.
[0038] [Figure 21] FIG. 21 shows the electrochemical stability of fluoromethane.
[0039] [Figure 22] FIG. 22 shows SEM images of lithium plating and stripping in a conventional liquid electrolyte. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0040] Section headings are used herein to improve readability and do not limit the features and scope of the described embodiments to a particular section. In this document, the term "exemplary" is used to mean "one example" and does not imply that the described features are in any way ideal or preferred, unless otherwise specified.
[0041] Electrochemical energy storage devices (e.g., batteries and double-layer capacitors) utilize ionically conductive electrolyte solutions to carry charge between positive and negative electrodes. For improved electrochemical stability of the device, the electrolyte solution uses a mixture of a certain amount of solvent and salt, additional components or additives. Common components include vinyl carbonate, fluoroethylene carbonate, lithium bis(oxalato)borate, among others. Such additives serve for surface modification of the electrodes, safety aspects, or other useful modalities.
[0042] The electrolyte components are generally liquids or solids at temperatures and internal device pressures typically encountered during device operation. Some components that are gaseous at such temperatures and pressures (e.g., carbon dioxide) may be added in small amounts to the electrolyte solution by bubbling through the electrolyte solution to saturate the solution with the gaseous component, but the amount is limited to less than 1 wt. % due to limited solubility.
[0043] The energy density of an electrochemical cell is proportional to the operating voltage and capacity. The capacity of the battery device depends on the capacity of the anode and cathode electrodes. Most commonly, the anode and cathode are both made from solid-state materials. However, certain liquid-based electrodes (i.e., catholytes) have also been used in primary battery devices. One advantage of using a liquid catholyte as a battery electrode is that it has a much higher capacity than a typical solid-state electrode. These types of primary electrodes typically reach the end of their life when the surface of the current collector, typically a high surface area carbon, becomes electrically or ionically insulated by the reaction products. It has been found that the voltage of these types of batteries is typically stable during discharge and varies depending on the potential difference between the reactants and the chemical reaction products in the battery. Therefore, increasing the capacity by improving the life of the high surface area current collector and increasing the voltage of the device would be useful in developing even higher energy density battery devices. Typically, these primary batteries also exhibit excellent low temperature characteristics because the catholyte is a low melting point material.
[0044] Certain electrolyte components that are exceptionally useful for electrochemical energy storage devices have limited practical application due to the gaseous nature of the components. Because the electrolyte components have high vapor pressures at standard room temperature and pressure, only a small fraction of the electrolyte components dissolves in the electrolyte solution and instead escapes as a gas. In addition, because the above-mentioned components have high vapor pressures at standard room temperature (approximately 20-22° C.) and standard pressure (approximately 1.01325 bar), the electrolyte components tend to volatilize easily.
[0045] In an exemplary embodiment, the electrochemical device may be operated at a pressure lower than the standard pressure so that the device is operated at a high internal pressure. This high pressure typically causes gaseous electrolyte components to remain in the liquid phase or to have a high gas concentration. By having the internal cell operated at a high pressure, more electrolyte components can be inserted into the cell. A higher weight percentage of such components is beneficial for the cell operation. For example, a higher amount of carbon dioxide in the cell may provide a better electrode surface layer on the positive or negative electrodes, suppressing parasitic electrochemical reactions from occurring. Another example is the addition of carbon dioxide to reduce the flammability of the electrolyte. Chemicals other than carbon dioxide, as described in this patent document, may have a similar effect. Another example is the addition of materials to reduce or increase the pressure of the electrolyte solution.
[0046] In some embodiments, when liquefied under pressure, many gaseous solvents act as solvents for electrochemical energy storage devices. Examples of such gaseous solvents include fluoromethane, difluoromethane, fluoroethane, difluoromethane, chloromethane, chloroethane, etc. Additional gaseous electrolyte components that can be added to these solvents in any amount to improve the device for advantageous performance include carbon dioxide, sulfur dioxide, carbon disulfide, oxygen, nitrogen, ammonia, etc.
[0047] A series of tests were conducted with various electrolyte components at different weight percentages in fluoromethane to test the decomposition of lithium metal, as shown in FIG. 1. Fluoromethane itself is known to decompose lithium metal into ceramic powder. By adding 10 weight percent carbon dioxide in fluoromethane under high pressure, lithium metal is highly protected from decomposition. This protection of lithium metal is due to the improved surface-electrolyte interface phase, which is electrically insulating and blocks further decomposition of the electrolyte components. FIG. 1 shows an exemplary optical image of lithium metal immersed for 5 days in fluoromethane with various electrolyte additive components at low weight percentages. The table shows the percent lithium mass change after immersing lithium in fluoromethane solvent with various additives for 5 days. As shown in FIG. 1, the lithium mass did not change when lithium was immersed in fluoromethane solvent with 10 weight percent carbon dioxide additive for 5 days. As a result, in some embodiments, lithium metal was immersed in fluoromethane with 10 weight percent carbon dioxide additive under high pressure for 5 days. By adding a certain amount of carbon dioxide, the lithium metal is protected from decomposition.
[0048] Figure 2 shows exemplary electrochemical performance of a lithium cobalt oxide (LiCoO2) cathode with a lithium metal anode and an electrolyte composed of 0.2 molar (M) lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) in a 9:1 weight ratio of fluoromethane:carbon dioxide. The cell was operated at high internal pressure, so a significant amount of carbon dioxide was in liquid form in the electrolyte.
[0049] Further, other advantageous properties of the exemplary electrochemical energy storage device include a relatively high electrolyte ionic conductivity capable of transporting ions. Furthermore, the electrolyte shows good suppression of undesirable dendrite formation during ion transport to the metal surface. FIG. 3 shows that the total charge passed is equal and for an equal amount of time at a positive 1 mA / cm 2 After the current density is negative 1mA / cm 2An exemplary lithium|lithium symmetric cell containing 0.2 M lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) salt in 19:1 fluoromethane:CO2 solvent is shown, where current density is cycled. This high current cycling typically shows dendrite formation and shorting of the two electrodes. It is shown that this dendrite growth does not occur and the cell does not short out as would otherwise be seen with a drop in voltage to near zero. This demonstrates the effectiveness of CO2 to form a good solid-electrolyte interface (SEI) on the lithium metal, allowing cycling at high rates and stable voltages and suppressing dendrite formation. Metals other than lithium may be used in the anode, including sodium, magnesium, potassium, etc., and may show similar characteristics. Suppressing dendrite formation is ideal, as it allows the use of lithium metal anodes with superior energy density in lithium batteries.
[0050] In some embodiments, it is possible to increase the conductivity of the electrolyte by increasing the dielectric constant caused by applying high pressure. Figure 4 shows an example electrolyte conductivity increase due to an increase in cell pressure. In this example, the conductivity and pressure of the electrolyte solution, 0.1M TBAPF6 in difluoromethane. At a temperature of +48°C, the pressure increases due to thermal expansion of the electrolyte, which occupies the entire volume of the cell, and then the pressure increases as the temperature increases. This increase in pressure increases the dielectric constant of the electrolyte, which then increases the conductivity of the electrolyte. Typically, the pressure in a conventional electrochemical device is minimal, since this pressure is adjusted to be approximately atmospheric pressure. An increase in the conductivity of the electrolyte can be seen by applying additional pressure by externally induced pressure during adjustment, for example by applying pressure by an insoluble gas (e.g., argon or nitrogen), or by the chemical composition of the electrolyte, such as, for example, including a high-pressure gas such as carbon dioxide that can dissolve in the electrolyte.
[0051] In some embodiments, the electrochemical energy storage device uses an electrolyte derived from a compressed gas solvent, which has a vapor pressure greater than atmospheric pressure of 1.01325 bar at 20° C., and the main electrochemical reaction at the cathode surface involves or involves sulfur or oxygen, producing lithium sulfide or lithium oxide, which is a reversible reaction, producing a rechargeable battery device. In some embodiments, the compressed gas solvent can exist in the housing in a liquid-only phase. For example, as shown in the pressure graph in FIG. 9A, during thermal expansion, the volume of the solvent in the liquid phase can occupy the entire cell housing. In some embodiments, the compressed gas solvent can exist in a combination of gas and liquid phases. For example, as shown in the pressure graph in FIG. 9A, at low temperatures, the pressure curve follows the normal solvent vapor pressure, which implies a combination of liquid and gas phases. When certain electrolyte solvents with high vapor pressure are used, these reactants are not soluble in contrast to conventional liquid electrolytes in which these reaction products are soluble. The solubility of these reactants limits the reversibility of these types of energy storage devices, as the active material is lost in the electrolyte solution itself. Such high vapor pressure solvents include fluoromethane or difluoromethane or carbon dioxide, tetrafluoroethane, and tetrafluoroethylene. It may be composed of tetrafluoroethane, difluoroethane, difluorochloromethane, and the like.
[0052] 5 illustrates an exemplary electrochemical device (500). The electrochemical device (500) includes an ionically conductive electrolyte (506) including one or more salts (512) and one or more compressed gas solvent solutions (508), each of which is in one of a liquid-only phase and a combination of gas and liquid phases, and the one or more compressed gas solvent solutions (508) have a vapor pressure greater than atmospheric pressure at room temperature. The electrochemical device further includes a housing (502) configured to encapsulate the ionically conductive electrolyte (506) and provide a pressurized condition for the one or more salts (512) and one or more compressed gas solvent solutions (508), and a pair of electrodes (504), (510) in contact with the ionically conductive electrolyte (506).
[0053] In another exemplary embodiment, the electrolyte solution may be designed to act as a liquid electrode or catholyte and also function as a chemical reactant based on a compressed gas catholyte that exhibits a vapor pressure greater than atmospheric pressure of 1.01325 bar at 20° C. In some embodiments, the compressed gas catholyte may exist in the housing in a liquid-only phase. For example, as shown in the pressure graph of FIG. 9A, during thermal expansion, the volume of the catholyte in the liquid phase may occupy the entire cell housing. In some embodiments, the compressed gas catholyte may exist in a combination of gas and liquid phases. For example, as shown in the pressure graph of FIG. 9A, at low temperatures, the pressure curve follows the normal catholyte vapor pressure, which implies a combination of liquid and gas phases. When used as a liquid electrode in a battery device, improved battery voltage, power, capacity, life or temperature performance is observed. Examples of such types of compressed gas solvents that can be used as liquid electrodes include thionyl fluoride, thionyl fluoride chloride, phosphoryl fluoride, phosphoryl fluoride chloride, sulfuryl fluoride, sulfuryl fluoride chloride, or any other compressed gas solvent that exhibits similarly improved battery characteristics, or a mixture of two or more compressed gas solvents, or a mixture of any number of compressed gas solvents with a conventional liquid solvent. Although liquid electrodes exist (e.g., sulfur dioxide that meets these criteria), these liquid electrodes are solubilized in the liquid solvent, lowering the overall vapor pressure of the solution below the requirements of devices based on the disclosed technology, which require only components with a vapor pressure greater than atmospheric pressure of 1.01325 bar at 20° C. other than the ionic salt components. Furthermore, some liquid cathodes generally react chemically to produce high vapor pressure substances that cause the overall solution to have a pressure even higher than atmospheric pressure. However, the high vapor pressure of these solutions is due to the products of the chemical reaction and not the reactants.
[0054] In an exemplary embodiment, a compressed gaseous solvent acts as the liquid cathode, such that the device described above can be configured to be a sealed, pressurized container. Pressure may be applied externally due to the vapor pressure of the solvent itself or by a pressure release. This pressure may vary due to temperature fluctuations, changes in the vapor pressure of the solvent, or externally applied pressure or pressure release.
[0055] In some embodiments, a salt is further added to the compressed gas solvent or compressed gas catholyte to produce a conductive solution. Examples of such salts that can be used include lithium hexafluorophosphate, lithium perchlorate, lithium tetrachloroaluminate, lithium tetragallium aluminate, lithium bis(trifluoromethanesulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium aluminum fluoride, lithium hexafluoroarsenate, lithium chloroaluminate, lithium chlorotitanate, lithium hexafluorotitanate, lithium tetrabromoaluminate, lithium tetrachloroborate, lithium tetrafluoroborate, lithium tetrachloroaluminate, sodium hexafluorophosphate, magnesium hexafluorophosphate, or mixed with any of the above types of liquid electrodes. Examples of suitable salts include those which form conductive solutions when heated.
[0056] These solutions may act as liquid cathodes and electrolytes between a metal anode and a cathodic current collector. Examples of such metal anodes may include lithium, sodium, calcium, magnesium, aluminum, iron, zinc, cadmium, lead, or similar metals. Examples of such cathodic current collectors may be composed in part of activated carbon, carbon black, carbon nanotubes, or similar high surface area materials.
[0057] Additionally, any number of additives may be added to the liquid cathode and electrolyte solutions to enhance battery performance by increasing voltage, capacity, life, temperature performance, or safety. Such additives may include lithium chloride, lithium fluoride, sodium fluoride, sodium chloride, bromine monochloride, bromine monofluoride, chloride, and fluoride.
[0058] Conventional liquid solvents that function as battery electrodes also act as battery electrolytes, typically made by adding salt to the liquid solvent to produce a conductive solution. One example of such a conventional battery device is comprised of a thionyl chloride solvent cathode that is mixed with lithium aluminum chloride to produce a conductive solution, a lithium metal anode and high surface area carbon black as a current collector for the liquid cathode, and an electrically insulating separator to prevent shorting of the cell. Such devices typically exhibit a voltage of about 3.65 V and an operating temperature range of -60 to +85°C. Traditionally, these types of batteries produce a protective layer on the lithium metal that prevents further chemical reaction between the lithium metal and the liquid cathode until a discharge is performed that destroys this protective layer. Reactions typical of this type of device generally result in lithium chloride products that are insoluble in the liquid solution and therefore precipitate within the pores of the carbon current collector, reducing the electrical conductivity between the liquid cathode and the carbon current collector, and ultimately may terminate the life of the device.
[0059] Exemplary electrochemical energy storage devices include liquid cathodes, such as fluorinated compressed gas solvents, to improve device performance. As a comparative example, a battery derived from a lithium anode and a thionyl fluoride or sulfuryl fluoride catholyte may provide a higher cell voltage than a conventional lithium anode and thionyl chloride battery due to the higher energy of reaction between the two species. Unlike the use of a liquid thionyl fluoride liquid cathode, which produces lithium chloride, the use of a thionyl fluoride liquid cathode, which has a higher reaction energy, would produce lithium fluoride. Furthermore, a thionyl fluoride liquid cathode may extend the life of a high surface area carbon current collector, since the particle size of the lithium fluoride precipitate is smaller compared to the lithium chloride precipitate, and therefore more lithium fluoride precipitate is required to passivate the entire high surface area carbon surface. Furthermore, a cathode derived from a thionyl fluoride compressed gas solvent may have a lower melting point than a conventional liquid-based cathode of thionyl chloride, further extending the operating range at low temperatures. Finally, the lower viscosity of thionyl fluoride compared to thionyl chloride may result in higher conductivity solutions, enabling higher power devices.
[0060] 6 illustrates an exemplary electrochemical device (600). The electrochemical device (600) includes an ionically conductive catholyte (606) including one or more salts (612) and one or more compressed gas catholyte solutions (608), each of which is in one of a liquid-only phase and a combination of gas and liquid phases, the one or more compressed gas catholyte solutions (608) having a vapor pressure greater than atmospheric pressure at room temperature. The electrochemical device (600) further includes a housing (602) configured to encapsulate the ionically conductive catholyte (606) and provide a pressurized condition for the one or more salts (612) and one or more compressed gas catholyte solutions (608), and an anode electrode (604) and a cathode current collector (610) in contact with the ionically conductive catholyte (606).
[0061] Electrochemical capacitors and Li-ion batteries have seen little change in their electrolyte chemistry since their commercialization limiting improvements in device performance. Combining excellent physical and chemical properties with high dielectric flow factors, the use of electrolytes based on solvent systems using components that are typically gaseous at standard conditions shows a wide potential range of stability and excellent performance over an extended temperature range. Electrochemical capacitors using difluoromethane show outstanding performance from -78 to +65°C and high operating voltages. The use of fluoromethane shows high coulombic efficiency of about 97% for cycling lithium metal anodes, combined with good cycling ability of 4V lithium cobalt oxide cathodes and operation at temperatures as low as -60°C with excellent capacity retention.
[0062] Electrochemical energy storage devices (e.g., electrochemical capacitors and batteries) are used in everything from communications to transportation. A significant increase in energy density is achieved over aqueous electrolytes by the development and use of electrolytes based on organic solvents that can operate at even higher voltages. Most electrolytes remain in the liquid and solid electrolyte systems, but few work well with electrolyte solvents that are typically gaseous at standard conditions. Although not used as an electrolyte, sulfur dioxide (T b = -10°C) and sulfuryl fluoride chloride (T b = +7.1 °C) have been used as catholytes in non-rechargeable primary lithium batteries, both as further co-solvents in electrolytes that are liquid at room temperature. b =-33.3°C) may be used as a liquid anode due to its ability to solvate alkali metals.
[0063] Many substances that are gaseous at room temperature are typically non-polar and are presumed to have small intermolecular attractions that inhibit them from condensing at room temperature or from solubilizing salts in a cooled or pressurized liquid state. While this may be generally true, there are many reasonably polar molecules that exhibit low London dispersion forces due to their small molecular size and gaseous state at room temperature. For example, the dielectric constant (ε) of dichloromethane is DCM,20℃ =8.9, T b = +40℃) is the dielectric constant (ε DFM,20℃ =14.2, T b = -52 °C), the former is a liquid at room temperature, whereas the latter is a gas. At low temperatures, or at moderate pressures, these types of polar gases have been shown to be capable of liquefying and solubilizing salts to produce liquefied gas electrolytes, and ion transport, redox phenomena, and other fundamental tests have been performed.
[0064] The use of liquefied gas electrolyte systems, consisting only of liquids that are gaseous at room temperature and atmospheric pressure, has been explored in rechargeable energy storage systems. Many potential liquefied gas solvents have been evaluated, but efforts have focused on hydrofluorocarbons with moderate dielectric constants in which salts can dissolve to produce conductive electrolytes. These electrolytes have demonstrated ultra-low temperature operation, high energy density in electrochemical capacitors, and high lithium plating and stripping efficiency for potential use with high capacity lithium metal anodes in batteries. Caution should be exercised, as hydrofluorocarbon solvents themselves are generally non-toxic, but can range from non-flammable to highly flammable, and combustion products may be toxic to humans. Additionally, these solvents exhibit low to high global warming potentials. Thus, these materials should be handled appropriately with further information given in supporting documents.
[0065] Physical and Chemical Properties of Liquefied Gas Solvents
[0066] The electrochemical stability of a range of liquid and liquefied gas solvents was qualitatively estimated by calculating the ionization potentials and electron affinities of these solvents, and is shown in Figure 14 and Table 1. The ionization potentials and electron affinities of liquefied gas solvents are shown in Figure 14. The ionization potentials and electron affinities of various solvent groups are calculated by DFT and shown in Table 1A.
[0067] Table 1A shows the ionization potentials and electron affinities of liquefied gas solvents. The ionization potential (IP) and electron affinity (EA) values of various solvent groups calculated by DFT. [Table 1A-1] [Table 1A-2]
[0068] Selected from solvents with optimal electrochemical stability and polarity, six promising liquefied gas solvents were identified and compared with conventional liquid solvents in Figure 8A. Figure 8A shows the ionization potentials and electron affinities calculated by DFT. The liquefied gas solvents include fluoromethane (FM), difluoromethane (DFM), fluoroethane (FE), 1,1-difluoroethane (1,1-DFE), 1,1,1,2-tetrafluoroethane (1,1,1,2-TFE), and 2-fluoropropane (2-FP). Liquid solvent: acetonitrile. Trill (ACN), propylene carbonate (PC), dichloromethane (DCM), tetrahydrofuran (THF), dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), ethylene carbonate (EC), vinyl carbonate (VC), fluoroethylene carbonate (FEC). Generally, these liquefied gas solvents exhibit improved oxidation-reduction resistance compared to conventional solvents. In particular, these calculations suggest that fluoromethane (FM) and difluoromethane (DFM) have improved electrochemical stability compared to tetrahydrofuran (THF) and ethylene carbonate (EC), which are known to have high stability with high reduction potential and oxidation potential, respectively. Figure 8B shows an electrostatic potential map. In Figure 8B, for comparison, the electrostatic potential map is superimposed on the physical structure of these solvents, and this may be used as a tool to qualitatively determine the electrochemical reduction stability of the solvents. The region with the highest electrostatic potential (the region with the strongest blue color) increases in the order of THF < FM < DFM < EC, which is in good correlation with the high electrochemical reduction stability of THF, indicating that FM also has good reduction stability. The region with the lowest electrostatic potential (the region with the strongest red color) increases in the order of EC < THF < FM < DFM, which is in good correlation with the relatively high solubility of small Li + cations, indicating that the solubility is better in FM than in DFM.
[0069] The dielectric constants of gaseous solvents (approximately ε = 10-15) are significantly lower than conventional liquid solvents, which may limit their ability to solubilize various salts. However, the viscosity of liquefied gas solvents at room temperature is also significantly lower than conventional liquid solvents. These properties are compared in Figure 8C for the liquefied gas solvents fluoromethane and difluoromethane. Figure 8C shows (C) relative dielectric constant, viscosity, and dielectric fluidity values. Both fluoromethane and difluoromethane have liquid viscosities approximately one-third lower than acetonitrile, which is commonly used for high power devices such as electrochemical capacitors. Due to these exceptionally low viscosities, ion mobility is expected to be very high in electrolytes composed of these solvents. The ratio of the dielectric constant to viscosity is used as a qualitative measure of electrolytic conductivity for a range of solvents. [ka] , i.e., the dielectric fluidity factors of the solvents, are compared in FIG. 8C. Liquefied gas solvents have been found to have superior dielectric fluidity factors compared to conventional liquid solvents, including acetonitrile, which generally exhibits some of the highest electrolytic conductivities. This qualitative comparison indicates that relatively high electrolytic conductivities can be expected for these solvents, which have only moderate dielectric constants. Furthermore, the viscosity of these solvents remains desirable even at very low temperatures, as shown in FIG. 15, which may allow for high electrolytic conductivities at temperatures that would freeze conventional solvents. FIG. 15 shows the viscosity of liquefied gas solvents as a function of temperature for selected liquefied gas solvents and a comparative conventional liquid solvent.
[0070] The vapor pressure curves of the six liquefied gas solvents tested over a range of temperatures are moderate and are compared in Figure 8D. Figure 8D shows the vapor pressure curves using the liquid range of various conventional and liquefied gas solvents. Among the solvents tested, fluoromethane and difluoromethane have the highest vapor pressures of 3.8 MPa and 1.8 MPa, respectively, at +25°C. The melting points of each solvent are below -100°C. Although the boiling points of these solvents are all below room temperature, the present study utilizes these solvents in a liquefied state below their own vapor pressure in a hermetically sealed cell, allowing electrolyte and cell characterization at high temperatures where the solvent is normally gaseous. Additionally, these solvents have fairly accessible supercritical points, as detailed in Table 1B. Since the surface tension is zero in the supercritical phase, these solvents may provide additional advantages such as excellent wetting or accessibility to nanopores in high surface area electrodes.
[0071] Table 1B shows the physical properties of the liquefied gas electrolytes tested. Vapor pressure, density, relative dielectric constant and viscosity values were taken as saturated liquids at +20° C. and saturated vapor pressure, except where indicated. [Table 1B]
[0072] Measurement of electrolytic conductivity
[0073] To determine the most promising solvents, electrolytic conductivity measurements of liquefied gas electrolytes were performed. Various liquefied gas solvents and salts were tested over a range of temperatures, and it was found that these electrolytes do not follow a typical conductivity versus temperature curve. In general, the electrolytic conductivity of liquid electrolytes increases approximately linearly with increasing temperature due to the decrease in solvent viscosity. However, liquefied gas electrolytes exhibit three distinct regions of conductivity over a wide temperature range, as shown in Figure 9A for 0.1 M TBAPF6 (tetrabutylammonium hexafluorophosphate) in difluoromethane. Figure 9A shows 0.1 M TBAPF6 in difluoromethane. The first region at low temperature shows a typical increase in conductivity with increasing temperature, which is due to the decrease in viscosity with increasing temperature. [ka] At moderate temperatures, there is a clear maximum in conductivity, which then gradually decreases. c,DFM = +78 °C), a decrease in conductivity is expected due to a decrease in the relative dielectric constant (ε DFM,-57℃ = 28.2, ε DFM,+20℃ =14.2). All solvents generally show a decrease in the dielectric constant with increasing temperature, but the tested solvents already have a relatively low dielectric constant at room temperature, and as the temperature increases, a significant amount of ion pair formation is likely to occur. At even higher temperatures, a sharp change in the conductivity is observed, dividing the second and third regions of the conductivity curve. This sharp change occurs well below the supercritical point, so it is unlikely that any related events contribute to this behavior. It was found that this sharp change in the electrolytic conductivity occurs simultaneously with a sudden increase in pressure of the electrolyte solution, beyond the normal solvent vapor pressure. This phenomenon can be explained by considering the thermal expansion behavior of the solvent. Indeed, at low temperatures, almost the entire volume of the measurement cell is filled with liquid solvent, while a small volume remains empty, usually filled with gaseous solvent by thermal evaporation. As the temperature increases, the volume of the liquid phase increases due to thermal expansion (ρ DFM,-60℃ =1.24g·cc -1 , ρDFM,+20℃ =0.98g·cc -1 ), the volume of the vapor phase decreases. At high temperatures, due to the thermal expansion of the solvent, the liquid phase occupies the entire volume of the cell, and further increase in temperature leads to a constant pressure increase due to the compression of the liquefied gas electrolyte. It should be noted that if the thermal expansion of the solvent is rather limited, rather high pressures can be observed. The increase in pressure in difluoromethane can result in a very significant increase in the dielectric constant of this solvent. Thus, the sharp change in electrolytic conductivity in the third region compared to the second region of Figure 9A is due to the enhancement of ion mobility from the increase in the dielectric constant of the solvent, which results from the pressure increase in the electrolyte system. This pressure-induced effect can be generalized to all electrolytes, but is a particularly noticeable effect due to the already moderate dielectric constant and high compressibility of this solvent.
[0074] Similar electrolytic conductivity phenomena will be observed for other liquefied gas electrolyte systems investigated. The electrolytic conductivity of 0.1 M EMITFSI (1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide) in several liquefied gas solvents is shown in Figure 9B and decreases in the order difluoromethane, fluoromethane, 1,1-difluoroethane, fluoroethane, 2-fluoropropane and 1,1,1,2-tetrafluoroethane. Figure 9B shows 0.1 M EMITFSI in various liquefied gas solvents. This follows the order of decreasing dielectric flow factors for the solvents already listed in Table 1B, lending credence to the proposed simple qualitative model (relative dielectric constants for fluoroethane and 2-fluoropropane were not available in the literature). As difluoromethane was found to exhibit the highest electrolytic conductivity, various salts were tested in this solvent and are shown in Figure 16. Figure 16 shows the electrolytic conductivity of the difluoromethane-based electrolyte. Electrolytic conductivity as a function of temperature for various salts in difluoromethane. TBAPF6 was found to exhibit the highest electrolytic conductivity in difluoromethane, and further testing of this electrolyte system was performed with various concentrations of salt and is shown in Figure 9C. Figure 9C shows the electrolytic conductivity of TBAPF6 in difluoromethane at various concentrations. The electrical conductivity of the liquefied gas electrolyte for TBAPF6 at concentrations between 0.02 and 0.50 M is considerably increased, indicating that this salt has good solubility in difluoromethane despite its relatively low dielectric constant. The electrolytic conductivity of a 0.50 M solution is 31 mS cm at +30 °C. -1 However, what is even more remarkable is that at -60°C it has a maximum conductivity of 13 mS cm -1 , and excellent low-temperature conductivity. Optimization of binary mixtures of liquid solvents with careful attention to conductivity, melting point, and potential freedom is shown, showing a similar electrolytic conductivity at -60 °C for 0.75 M TEABF4 (tetraethylammonium tetrafluoroborate) in acetonitrile:methyl formate 3:1, although the potential freedom of this electrolyte was limited. Figure 9C shows that at various concentrations, the conductivity curves show the same general three regions of electrolytic conductivity across the temperatures measured. The characteristic change in the slope of the conductivity curve in the first region, most notably at 0.5 M concentration of TBAPF6, can be attributed to the increased ion pairing that is expected to occur in medium permittivity solvents with these high salt concentrations. The temperature dividing the second and third regions changes gradually from +35 °C to +79 °C for salt concentrations between 0.02 M and 0.5 M. This can be understood by the low thermal expansion coefficient of this solution with increasing salt concentration. More heat energy would be required to cause volume expansion and create a constant volumetric increase in pressure, which would result in an abrupt change in electrical conductivity.
[0075] Difluoromethane is known to have exceptional electrolytic conductivity with many salts, and this solvent was found to be unable to solubilize lithium salts. This is probably due to the steric bulk of the highly electronegative fluorine atoms of the neighboring solvent molecules, which prevents Li +This prevents the formation of a solvation shell around the cation. Further studies have shown that lithium bis(trifluoromethane)sulfonimide (LiTFSI) can be solubilized only in the monofluorinated liquefied gas solvents fluoromethane, fluoroethane, and 2-fluoropropane. This indicates that these monofluorinated solvents are more basic and Li + This is consistent with the suggestion that fluoromethane has a binding energy to cations, and is consistent with the electrostatic potential map already shown for the solvents in Figure 8B. The electrolytic conductivity of these three monofluorinated liquefied gas solvents with 0.1 M LiTFSI is compared in Figure 9D, which shows 0.1 M LiTFSI in various monofluorinated liquefied gas solvents. Fluoromethane is shown to have the highest electrolytic conductivity of the three solvents, as would be expected from its exceptionally high dielectric flow factor: 1.2 mS cm -1 The maximum conductivity is observed at -22°C and 1.1 mS cm at -60°C. -1 For comparison, a low-temperature electrolyte of LiPF6 in a mixture of carbonate and methyl acetate has a low-temperature conductivity of 0.6 mS cm at -60 °C. -1 Although the electrolytic conductivity was relatively poor across the cell due to a non-ideal solvent system, the electrolytic conductivity at higher concentrations was only slightly improved with the LiTFSI salt. At higher temperatures, the electrolytic conductivity increased when fluoromethane reached its critical temperature (T c,FM = +44°C), there is a rapid drop in conductivity due to precipitation of salts from the electrolyte, a useful safety feature in lithium-based electrolytes.
[0076] Electrochemical Capacitor
[0077] Since difluoromethane exhibits the highest electrolytic conductivity for non-lithium based salts, the electrochemical stability of this solvent was tested. Figure 10A shows the cyclic voltammetry curves of 0.1 M TEABF4 in difluoromethane at both +25°C and -60°C. At +25°C, a potential spread of 5.70 V is observed. The positive potential limit of 2.47 V vs. Pt coincides well with the potential limit for anion oxidation. The significant reduction current observed at an onset potential of -3.23 V vs. Pt is followed by a high reduction current in the reverse sweep direction, probably due to the corrosion of the working electrode. These The potential limits are in good agreement with previous results using similar salt systems. At -60 °C, the electrolyte exhibits an excellent electrochemical freedom of 6.83 V, which is wider than that at +25 °C due to the slower reaction kinetics at the lower temperature.
[0078] A commercial electrochemical capacitor of nominal capacitance of 350F was tested with 0.5M TEABF4 in difluoromethane and, for comparison, with a standard liquid electrolyte consisting of 1M TEABF4 in acetonitrile, both tested under identical mechanical cell conditions and immersed in the electrolyte. The capacitance and resistance over a range of temperatures are shown in FIG. 10B. FIG. 10B shows capacitance and resistance measurements of symmetrical 350F electrochemical capacitors with 0.5M TEABF4 in difluoromethane and 1M TEABF4 in acetonitrile at temperatures from −78° C. to +65° C. The capacitance was measured from 2.4 V to 1.2 V during constant current discharge. The resistance was measured by the iR drop between the voltage hold and the constant current discharge step. At +25° C., the capacitance of both devices is about 375 F and remains fairly constant over the temperature range tested, dropping only slightly to about 350 F at lower temperatures. The resistances of 8.5 mΩ and 11.0 mΩ at +25°C for the difluoromethane and acetonitrile devices, respectively, highlight the high electrolytic conductivity and applicability of the electrolyte to electrochemical capacitors for high power applications. At lower temperatures, the acetonitrile-based device slowly increased in resistance to 14.9 mΩ at -40°C, just above its freezing point, while the difluoromethane-based device decreased in resistance to 5.8 mΩ at -20°C. This is consistent with electrolytic conductivity measurements that show a maximum in electrolytic conductivity around this temperature range. At even lower temperatures, the resistance increases slowly and is comparable at -78°C and +25°C, highlighting the excellent low temperature performance of this electrolyte. This operating temperature is almost 40°C lower than the nominal value of commercial acetonitrile-based electrochemical capacitors and is not exceeded by other low temperature electrolyte formulations. At higher temperatures of +65°C, the resistance increases slightly to 13.4 mΩ. Device cycling performance was also tested with difluoromethane in the supercritical phase and is shown in Figure 17. Figure 17 shows the performance of an electrochemical capacitor. The percent change in capacitance and resistance of an electrochemical capacitor over multiple cycles at various temperatures.The capacitance of the device is maintained, but the resistance of the electrolyte increases considerably at +90°C (increase of about 1500%) due to the precipitation of salts from the solvent, caused by the decrease in the dielectric constant. At lower temperatures, the resistance drops to the nominal value as the salts solubilize back into solution, showing a small decrease in capacitance due to the accelerated cell decomposition at higher temperatures.
[0079] To determine whether the novel difluoromethane-based electrolyte provides an advantage in terms of energy density, electrochemical capacitors were tested at elevated voltages and temperatures of 3.0 V and +65° C. for 1500 hours, as shown in FIG. 10C. FIG. 10C shows capacitance and resistance measurements of a symmetrical 350F electrochemical capacitor with 0.5 M TEABF4 in difluoromethane and 1 M TEABF4 in acetonitrile using an accelerated life test at 3.0 V from −60° C. to +65° C. Capacitance was measured from 2.4 V to 1.2 V during constant current discharge. Resistance was measured by the iR drop between the voltage hold and constant current discharge steps. Devices using the acetonitrile-based electrolyte failed rapidly under these accelerated conditions, showing a significant increase in resistance and a decrease in capacitance, consistent with previous studies of electrochemical capacitors under similar conditions. However, the difluoromethane devices show little capacitance drop or little increase in resistance under the same conditions. Similarly, a 3.0V test is performed at -60°C to test the low temperature lifetime of the devices, showing little change in capacitance or resistance. Although already shown to have comparable capacitance, the increase in voltage from 2.7V (for a typical acetonitrile device) to 3.0V represents a 23% increase in energy density, providing advantages for a range of electrochemical capacitor applications such as cold engine cranking, vehicle start-stop, and hybrid buses.
[0080] Rechargeable Lithium Metal Batteries
[0081] Due to the high reducing potential of lithium (-3.04 V vs. NHE), a thin, electrically insulating, but Li-ion conducting solid electrolyte interface phase quickly forms on lithium metal upon contact with many commonly used liquid solvents. Optical images of the chemical products obtained after immersion of lithium metal in each of the liquefied gas solvents are shown in Figure 18. Figure 18 shows optical images of lithium metal after immersion in the liquefied gas solvents. Reaction products resulting from immersion of lithium metal in six different liquefied gas solvents, with exposed lithium metal (mostly remaining in the image) for comparison. All samples were immersed in the solvent until all chemical reaction activity was found to have ceased, the times being shown in Table 2. Polyfluorinated solvents (difluoromethane, difluoroethane, and 1,1,1,2-tetrafluoroethane) each produce a stable SEI on the lithium metal, preventing further decomposition of the lithium metal or the solvent. Although extensive characterization of these interfaces was not performed for these chemical products, the SEI is believed to be composed of a variety of fluoropolymers, notably. Monofluorinated solvents (fluoromethane, fluoroethane, 2-fluoropropane) are capable of solubilizing lithium salts, each of which completely decomposes lithium metal into a powder form without producing a stable SEI. As detailed in Table 2, the reaction time for complete decomposition of lithium metal at room temperature in liquid fluoromethane is significantly slower than in liquid fluoroethane or 2-fluoropropane.
[0082] Table 2 shows a summary of the results of the lithium metal immersion test. The characteristics of the reactants obtained by immersing lithium metal in various solvents at 25°C. 2 A lithium metal plate was used. The lithium metal was immersed and the reaction was completed. [Table 2]
[0083] The chemical reduction of fluoromethane by lithium metal is hypothesized to be as follows:
[0084] CH3F+Li → LiF+CH3
[0085] Li+CH3 →CH3Li
[0086] CH3 + CH3 → C2H6
[0087] Among the chemical products, LiF and CH3Li were observed in the X-ray diffraction (XRD) and Fourier transform infrared spectroscopy (FTIR) spectra shown in Figures 19 and 20, respectively, supporting this reaction scheme. Figure 19 shows the XRD spectrum of lithium metal after immersion in liquefied gas solvents. Spectrum of lithium metal after immersion in a mixture of fluoromethane, carbon dioxide, and FM:CO2 19:1 for 5 days. During the lithium immersion, the solvents were all in liquid state at +25°C. Figure 20 shows the FTIR spectrum of lithium metal after immersion in liquefied gas solvents. Spectrum of lithium metal after immersion in a mixture of fluoromethane, carbon dioxide, and FM:CO2 19:1 for 5 days. During the lithium immersion, the solvents were all in liquid state at +25°C. The spectra after immersion in the mixture for 5 days. During the lithium immersion, the solvent was all in liquid state at 25 °C. FTIR peaks of methyllithium were also identified. The rate of lithium decomposition in fluoromethane is relatively slow, and since it is the solvent with the highest electrolytic conductivity with lithium salts as can be seen in Figure 9D, we investigated how to solubilize the lithium metal surface. The use of carbon dioxide in the additive amount in fluoromethane was found to be sufficient to stabilize the lithium surface due to the creation of a stable lithium carbonate surface layer. The creation of this stable interface is shown in Figures 19 and 20, which show that the addition of 5 wt% carbon dioxide results in almost no LiF or CH3Li in the SEI layer at the macroscopic level. Carbon dioxide is an effective additive for use in Li-ion batteries, but its solubility in common organic solvents is limited to about 0.5 wt% and is strongly temperature dependent. Conversely, carbon dioxide and fluoromethane are miscible solvents, and it may be possible to use this highly effective additive in next generation batteries.
[0088] The electrochemical stability of the fluoromethane-based liquefied gas electrolyte was determined by cyclic voltammetry with the addition of carbon dioxide to produce a stable SEI layer on the lithium metal, and is shown in Figure 11A and in more detail in Figure 21. Figure 11A shows the results of the cyclic voltammetry performed at +25 °C and -60 °C with a voltage sweep rate of 1 mV sec -1 , the oxidation potential limit is 200 μA cm -2 Figure 21 shows the cyclic voltammetry curves of 0.1 M LiTFSI in fluoromethane, performed with a cutoff current of 1000 Hz. Figure 22 shows the electrochemical stability of fluoromethane. Cyclic voltammograms of 0.2 M LiTFSI in FM:CO2 19:1. WE=Pt, CE and RE=Li metal, sweep rate=1 mV·sec -1 .
[0089] The electrolyte is limited by oxidation at 5.57 V and 5.79 V vs. Li at +25 °C and -60 °C, respectively, indicating a slower rate of solvent oxidation at low temperatures. Carbon dioxide reduction is found to begin at 2.1 V vs. Li, which is in good agreement with the literature. Typical lithium metal plating and stripping peaks are observed centered near 0 V vs. Li. No cathodic upper potential deposition peak is observed for the lithium and platinum alloys due to simultaneous carbon dioxide reduction, but two anodic upper potential deposition stripping peaks are observed. The larger peak is followed by a smaller peak at 0.58 V and 1.32 V, respectively. At -60 °C, a relatively high overpotential for lithium nucleation is also observed, with lithium decomposition beginning at -0.39 V vs. Li.
[0090] Lithium metal has the highest gravimetric capacity of all possible anodes (3863 mAh g), although it is known to suffer from poor coulombic efficiency and significant dendrite formation in conventional electrolytes. -1), many attempts are still being made to realize this anode in rechargeable batteries. When using low viscosity solvents, increasing pressure at the electrode and surface coating of LiF are all promising methods to improve the cyclability of lithium metal anodes and reduce the severity of dendrite formation. The exceptionally low viscosity and high vapor pressure of LiF chemical reduction products are all intrinsic properties of fluoromethane liquefied gas solvent. To investigate the effectiveness of the proposed electrolyte system in realizing lithium metal anodes, the coulombic efficiency of lithium plating and stripping was measured on polished stainless steel electrodes. As shown in Figure 11B, the fluoromethane-based electrolyte exhibited an aggressive current of 1 mA cm -2 With plating and stripping rates of 1 coulomb cm per cycle -2 The cell shows a stable and high coulombic efficiency of about 97% during 400 cycles with 10 ... The cycles were stopped at 0° C. and the stainless steel substrate was examined using a scanning electron microscope. The surface morphology of the lithium layer deposited from the fluoromethane-based electrolyte is found to be very uniform with micron-sized granular features and no dendrite growth (FIG. 11C). This is in contrast to the highly polymeric and dendritic surface observed from the liquid electrolyte cycles (FIG. 22). FIG. 11C shows an SEM of the fluoromethane SS316L working electrode after 400 cycles, imaged at a 30° tilt in the lithiated state. FIG. 22 shows an SEM image of lithium plating and stripping in a conventional liquid electrolyte. SEM image of the stainless steel working electrode used in the lithium plating and stripping experiments after 400 lithium plating and stripping cycles, imaged at a 30° angle in the lithiated state. Furthermore, the thickness of the lithium layer deposited in the fluoromethane and comparative liquid electrolytes was found to be about 60 μm and about 460 μm, respectively, reflecting the significantly better coulombic efficiency of the novel electrolyte system. The coulombic efficiency of lithium plating and stripping is compared to reported values for diethyl ether:tetrahydrofuran 95:5 (98%) (34), 2-methylfuran (97%) (35), and 1,2-dioxolane (98%) (36). High efficiency in these systems is only seen when using the toxic lithium hexafluoroarsenate (LiAsF6) salt, which is reduced at the lithium metal surface to produce a LiF passivation layer. In the fluoromethane system, the solvent itself, when reduced, forms a LiF layer, eliminating the need for LiAsF6 salt. In addition, reduction of carbon dioxide to produce lithium carbonate has been shown to improve the impedance and cyclability of lithium metal anodes, and this was used to stabilize the electrodes in this study. More recently, other electrolyte systems have been shown to have high lithium plating and stripping efficiencies without the use of LiAsF6, but none have demonstrated robust oxidation stability for use with conventional 4 V cathode systems, due to the poor stability of these ether-based electrolytes at high potentials (38).These electrolytes are mostly limited to cathode chemistries with low potential and limited oxidation of these solvents, but the ability to use lithium metal anodes with high voltage intercalation cathodes would significantly increase energy density as well.
[0091] A lithium cobalt oxide (LiCoO2) cathode was used to demonstrate high oxidation stability and compatibility of fluoromethane-based liquefied gas electrolyte with conventional cathode materials. Fluoromethane and conventional liquid-based electrolyte systems were used for comparison to test this cathode under identical cell conditions. All charge and discharge of the cell was performed at a fixed temperature, rather than charging at a high temperature and discharging at a low temperature. Electrode performance in both electrolyte systems is shown for a number of cycles at various temperatures and C-rates (Figure 11D) and corresponding curves of voltage vs. discharge capacity (Figure 11E). Figure 11D shows the discharge capacity at various temperatures and C-rates. Figure 11E also shows the voltage vs. discharge capacity at various temperatures and C / 10 rate. At +25°C, the discharge capacity at C / 10 rate was very similar, approximately 133 mAh g -1At higher rates, the performance of the liquid electrolyte system is significantly better than that of the fluoromethane-based electrolyte, showing 87.2% and 81.2% capacity retention at 1C rate, respectively. However, at lower temperatures, the high rate performance of the fluoromethane-based electrolyte is significantly better. At -10°C and C / 10 rates, the fluoromethane and liquid electrolytes show 98.3% and 86.2% discharge capacity retention, respectively, versus +25°C. At higher rates or lower temperatures, the liquid electrolyte cannot be cycled properly due to high cell impedance. In contrast, cells utilizing the fluoromethane-based electrolyte cycle at higher rates at a variety of temperatures, and most notably, they show excellent capacity retention of 60.6% at -60°C and C / 10 rate, where conventional liquid electrolytes typically freeze out. This compares favorably with a specially developed low-temperature liquid electrolyte that has a discharge capacity retention of 43.5% at -60°C and C / 10 rate using a significantly larger capacity full cell. The impedance spectra of the cells at each temperature are shown in Table 1. The torque is shown in Figure 7 and the fitted parameters are given in Table 3. Figure 7 shows the electrochemical impedance spectra of lithium metal LiCoO2 cells. Electrochemical impedance spectra of cells with LiCoO2 and lithium metal as the cathode and anode, respectively, with electrolytes derived from fluoromethane (top) and conventional liquid (bottom). Spectra obtained at a cell voltage of 4.1 V. The fitted impedance data are shown in Table 3. The additional RC circuit at high frequencies is an artifact of the wire and metal contacts immersed in the electrolyte solution due to the inherent construction of the high pressure cells, so the fitted parameter R1 remained constant for each cell at all temperatures.
[0092] The stability of the fluoromethane-based electrolyte system is compared with liquid electrolytes at +25 °C and C / 2 rate in Figure 11F, which shows the discharge capacity and coulombic efficiency for a LiCoO2 electrode with a lithium metal anode cycled at C / 2 rate. Both electrolytes showed very similar stability, with the fluoromethane-based electrolyte showing 96.7% capacity retention after 100 cycles, indicating the high compatibility of this electrolyte system with conventional 4V cathodes.
[0093] Table 3 shows the impedance spectroscopy fitting parameters for the lithium metal LiCoO2 cell. Electrochemical impedance spectroscopy fitting parameters for cells using lithium metal anode and LiCoO2 cathode in two types of electrolytes at various temperatures. The fitted circuit and full impedance spectra are shown in Figure 23. [Table 3-1] [Table 3-2]
[0094] The low electrical conductivity of conventional liquid electrolytes is not the main cause of the limited low-temperature performance of Li-ion cells. The true cause of these limitations is likely due to charge transfer or solid electrolyte interface impedance, which is sensitive to the type of electrode and electrolyte used. Since identical anodes and cathodes were used in these tests, the high performance of fluoromethane-based electrolytes at such low temperatures can be attributed to the significantly improved SEI layer on the electrodes. To further investigate the electrode-electrolyte interface observed with fluoromethane-based electrolytes, X-ray photoelectron spectroscopy (XPS) analysis was performed on both the lithium metal anode and the LiCoO2 cathode. As can be seen in Figure 12, the lithium metal surface immersed in fluoromethane is composed of a significant portion of LiF and CH3Li, with a small amount of Li2CO3 signal from impurities in the lithium metal. The addition of carbon dioxide to stabilize the surface further adds a significant amount of Li2CO3 component to the SEI and less CH3Li component, which is consistent with the XRD and FTIR analysis. After cycling, the surface composition shows little chemical change and retains a very ceramic-like SEI composed primarily of LiF and Li2CO3, in contrast to the very polymer-like SEI produced on lithium metal surfaces immersed in conventional carbonate-based electrolytes. The formation of a thin Li2CO3 layer by carbon dioxide reduction and the high mobility of lithium ions through the grain boundaries of the very ceramic surface both result in a very low impedance through the anode SEI layer. Furthermore, a highly chemically uniform interface, such as that found in fluoromethane-based electrolytes, is believed to contribute to a more uniform current distribution and prevent dendrite formation.
[0095] Although the improved anode is expected to improve cell performance, previous studies have shown that at low temperatures, significantly higher impedance occurs at the cathode but not at the anode (44). The chemistry of the cathode-electrolyte interface was examined by XPS and is shown in Figure 13. Comparing the XPS spectra of the LiCoO2 electrode before and after cycling, there are striking differences. Other than evidence of a small amount of residual LiTFSI salt, there are no changes in the Li 1s, C 1s, F 1s, and Co 2p spectra for the electrode cycled in the fluoromethane-based electrolyte. In contrast, the electrode cycled in the conventional liquid electrolyte shows a PF6 - There is a noticeable increase in LiF at the electrode surface from the decomposition of the anion. The O 1s shows a typical increase in polymeric species consistent with other studies, and the changes occurring in the O 1s spectrum of electrodes cycled in fluoromethane-based electrolytes are not clear. Since carbon dioxide is expected to be stable at the potentials seen at this electrode surface and no other oxygen sources are present, the increase in peaks seen in the O 1s spectrum can be attributed to changes in the surface oxygen of the LiCoO2 electrode and is not related to the generation of an additional surface layer on the electrode. It is concluded that both the improved SEI on lithium metal and the cathode with little or no SEI contribute to the exceptional low temperature performance of lithium batteries using these liquefied gas electrolytes.
[0096] conclusion
[0097] A combination of excellent physical and chemical properties has demonstrated that liquefied gas electrolytes derived from hydrofluorocarbons are suitable for energy storage devices. The low melting points and high dielectric flow factors of these liquefied gas solvents allow for exceptionally high electrolytic conductivity over a range of temperatures. The high performance of electrochemical capacitors and lithium batteries at temperatures as low as -78°C and -60°C, respectively, indicates potential applications in aviation and upper atmospheric applications. Comparable conductivity and performance to conventional electrolytes at moderate temperatures have also been demonstrated, making them applicable to more mainstream applications such as hybrid and electric vehicles. The use of difluoromethane as the electrolyte solvent has demonstrated the operation of electrochemical capacitors at high voltages under accelerated life conditions, corresponding to a 23% increase in energy density. The use of fluoromethane as the electrolyte solvent has demonstrated high coulombic efficiency of about 97% for plating and stripping of lithium metal, no dendrite formation, and compatibility with conventional 4V LiCoO2 cathodes, providing a promising route to develop high energy density rechargeable lithium metal batteries.
[0098] material and method
[0099] Materials: In one example, fluoromethane (99.99%) and difluoromethane (99.99%) were obtained from Matheson Gas, fluoroethane (97%), 1,1-difluoroethane (99%), 1,1,1,2-tetrafluoroethane (99%) and 2-fluoropropane (98%) were obtained from Synquest Labs, and carbon dioxide (99.9%) was obtained from Airgas. To minimize release to the atmosphere, all gases were stored in high-pressure refrigerated recovery tanks after use. Salts such as tetraethylammonium hexafluorophosphate (99.9%) and lithium bis(trifluoromethane)sulfonimide (99.9%) were purchased from BASF, while all other salts (electrochemical grade) and acetonitrile (99.8%, anhydrous) were purchased from Sigma-Aldrich. For comparative testing, a liquid electrolyte consisting of 1M LiPF6 in EC:DEC 1:1 by weight was used (LP40, BASF). FTIR For the measurements, dimethyl carbonate (≥99%, anhydrous) and Nujol oil were purchased from Sigma-Aldrich. Acetonitrile and dimethyl carbonate were dried over molecular sieves before use, but all other materials were used as received.
[0100] In one example, lithium cobalt oxide, carbon black, and lithium metal for the lithium battery electrodes were purchased from Sigma-Aldrich, Timcal, and FMC, respectively. In the lithium battery and lithium plating and stripping experiments, the electrodes were electrically isolated using a piece of porous 20 μm polypropylene separator (Celgard 2075). A commercial electrochemical capacitor jelly roll (nominal 350F) was donated by Maxwell Technologies and had never been in contact with an electrolyte solution before.
[0101] Measurement of electrolytic conductivity
[0102] We measured the electrolytic conductivity of four types of electrodes. In brief, we used electrodes made of custom-made borosilicate glass with a thin layer of platinum sputtered on it. The cell constants were measured in the range of 0.1 to 100 mS cm with a measurement accuracy of ±6%. -1 The thin-film electrodes ensured that their geometry, and therefore their cell constant, did not change under the high pressures arising from the electrolytes tested.
[0103] Electrochemical Capacitor
[0104] For electrochemical capacitor testing, the jelly rolls were dried overnight at +180°C under high vacuum. To obtain accurate resistance measurements, a custom cell was designed to perform 4-wire measurements on the jelly rolls. All metal contacts were made from aluminum to avoid corrosion issues during cell testing. All cell assembly was performed under an argon atmosphere.
[0105] Resistance (DCR) measurements were calculated from the instantaneous iR drop (obtained with a high resolution potentiostat) resulting from a discharge current of 0.5 amps after holding at 3 V for 1 hour. Capacitance was measured as follows.
[0106] Capacitance = I (t2-t1) / (V2-V1)
[0107] where I, V2 and V1 were set to -0.5 amps, 2.4V and 1.2V, respectively.
[0108] Rechargeable Lithium Metal Batteries
[0109] For rechargeable lithium metal battery testing, electrode slurries consisting of LiCoO2:carbon black:PVDF binder in a weight ratio of 8:1:1 were mixed with an appropriate amount of N-methyl-2-pyrrolidone (NMP) solvent on a 25 μm thick stainless steel 316L foil using a doctor blade. The thickness of the coated active electrode after cold calendering was approximately 40 μm thick. The active material loading was approximately 0.9 mAh cm.-2 or 6.6 mg cm -2 (The theoretical capacity was 137 mAh g when cycled between 3.5 V and 4.1 V. -1 For cell testing, the 0.31 cm 2 Electrodes were used. Lithium metal was purchased from FMC and was cleaned and stripped on glass slides, wound with polyethylene rods, and polished to a mirror finish prior to all experiments. The electrodes were electrically isolated with a single porous 20 μm polypropylene separator and placed inside custom-made coin cells constructed from high density polyethylene with stainless steel 316L current collectors for both electrodes. All cells were The assembly was carried out under an argon atmosphere.
[0110] For lithium plating and stripping coulombic efficiency testing, cells were similarly prepared, except that instead of using a LiCoO2 electrode, lithium was plated directly onto a stainless steel 316L current collector, which was used as the working electrode and polished to a mirror finish. In all tests, all wetted metal components were stainless steel 316 to avoid corrosion issues.
[0111] Addition of electrolytes
[0112] In an exemplary embodiment, to create a liquefied gas electrolyte solution, a predetermined weight of salt is first preloaded into a high voltage cell (e.g., a stainless steel cell) along with a capacitor or battery device (e.g., a pair of electrodes) and sealed under an argon atmosphere. The predetermined weight of salt may be determined based on the volume of compressed gas solvent and the concentration of the salt. For example, for a 0.2 M solution in a 2 liter volume of compressed gas solvent, 0.2 moles of salt are required, where 1 mole is 6.022x10 231 molecule. The cell was then cooled to a temperature lower than the temperature of the compressed gas solvent source. A controlled amount of solvent was evaporated from the source using either a mass flow controller (MKS) or mass flow meter through a tube connected to the cell and condensed in the cell, which was then sealed. In some embodiments, the cell is sealed using an attached valve. In some other embodiments, the cell is sealed using a plug or a welded cover. A controlled amount of solvent may be selected and the salt may be diluted to a predetermined concentration (e.g., 0.2M LiTFSI). For the comparative test, a conventional liquid electrolyte was added under an argon atmosphere before sealing the cell. The cell for the comparative test with liquid electrolyte was otherwise mechanically identical to the cell with the liquefied gas electrolyte system, and the electrodes were similarly immersed in the electrolyte solution.
[0113] Determination of thermal and electrochemical properties
[0114] For thermal testing, the cell was allowed to thermally equilibrate in a temperature chamber (Espec) before testing began. For testing at -78°C, dry ice was used to cool the cell. Temperature measurements were taken using a K-type thermocouple with an uncertainty of ±2°C, and pressure measurements were recorded from a digital pressure transducer (Omega Engineering) with an uncertainty of ±2% for the measured pressure. Temperature and pressure measurements were recorded using a digital data acquisition system (Agilent).
[0115] All electrochemical tests were performed in a high-pressure stainless steel cell fitted with electrical feedthroughs electrically connected to the test electrodes. -1 Cyclic voltammetry experiments were performed at a sweep rate of 1000 s. The non-lithium based electrolytes used sputtered platinum counter and reference electrodes. The lithium based electrolytes used lithium metal counter and reference electrodes. All electrolytes were measured on a 1 mm2 area ceramic plate on borosilicate glass. 2A sputtered platinum working electrode (the exposed area is defined by a silicon dioxide passivation layer with a thickness of about 250 nm) was used. Separate platinum working electrodes were used at each temperature for the anodic and cathodic potential ranges and to avoid any influence from previous polarization of the working electrode. The current was 200 μA cm -2 The potential degrees of freedom were calculated when the potential was increased beyond 0.5 V. Electrochemical impedance measurements of the cells were performed using a sinusoidal probe voltage of 5 mV and the spectra were fitted using ZView software. All electrochemical capacitor cycling, cyclic voltammetry and impedance measurements were performed using an SP-200 potentiostat (Bio-Logic).
[0116] Lithium battery cells were cycled using a battery cycler (Arbin). For the CoO2 cell tests, cycling consisted of 100% depth discharge from 3.5 to 4.1 V for all measurements. For lithium plating and stripping experiments, one cycle consisted of 1 mA cm -2 current density of 1 coulomb cm -2 Lithium metal is plated with Li, and then the potential of the working electrode becomes Li / Li + 1 mA cm until the load rises above 1 V -2 At this point the current was immediately restored and the next cycle was performed. The coulombic efficiency was simply calculated as:
[0117] Efficiency%=100·(Q strip )·(Q plate ) -1
[0118] In the formula, Q strip is the amount of charge passed during the lithium stripping cycle, and Q plate is the amount of charge plated in each cycle (1 coulomb cm -2 ).
[0119] Material characterization
[0120] Powder X-ray diffraction (XRD) of the samples was collected on either a Bruker D8 or Bruker D2 Phaser using Cu Kα radiation with a scan rate of approximately 0.02° s -1 , with a wavelength λ = 0.154 nm and continuous scanning of the detector covering angles from 10.0° to 80.0°. Air-sensitive samples were sealed in polyethylene heat-sealed bags under an argon atmosphere and the background was included in the XRD background spectrum.
[0121] Fourier transform infrared (FTIR) measurements were performed on a liquid nitrogen cooled Nicolet 6700 Analytical MCT FT-IR Spectrometer using an Attenuated Total Reflectance (ATR) attachment (single bounce, Diamond / ZnSe crystal). For lithium metal measurements, samples were immersed in Nujol mineral oil under an argon atmosphere. The samples were then transferred to sealed vials and immediately clamped to the ATR crystal using a polyethylene plastic liner. This allowed the Nujol oil to spread around the samples, protecting them from the atmosphere. Measurements were run for several minutes to avoid changes in the FTIR spectrum due to reactions with the atmosphere.
[0122] Scanning electron microscope images were taken on an FEI XL30 SFEG using Ultra High Resolution (UHR) scanning mode at a beam energy of 5 keV. To minimize air exposure, the imaged lithium metal samples were quickly transferred from the sealed vial to the SEM chamber under argon atmosphere. To measure the thickness of the films, a sharp blade was used to cut the film down the center and the cross section was observed in the SEM at a 30° angle.
[0123] The AXIS Supra manufactured by Kratos Analytical Inc. was used as the X-ray source, with monochromated Al Kα radiation (hν=1486.7 eV) at a base pressure of 10 -8 X-ray photoelectron spectroscopy measurements were performed at 1000 × 1000 Pa. To avoid moisture or air exposure, the XPS spectrometer was directly connected to an argon-filled glove box in which samples were prepared for analysis. The analysis area for all XPS spectra is 300 × 700 μm 2 XPS was performed using a high resolution scan with a pass energy of 15 kV and a step size of 0.05 eV, collected after a survey scan with a step size of 1 / 0 eV in the lithium 1s, carbon 1s, oxygen 1s, nitrogen 1s, fluorine 1s and cobalt 2p regions. All acquired XPS spectra were analyzed by CasaXPS software and calibrated using the hydrocarbon C1s signal at 284.6 eV. A nonlinear Shirley type background was used to perform the core peak. The curves were weighted using a minimum The data were smoothed using a squared-square algorithm and fitted to a straight line with a geometry composed of 70% Guassian and 30% Lorentzian. The lithium metal samples were not washed, but in the case of liquid electrolyte, they were dried to remove most of the electrolyte from the surface. Prior to XPS analysis, the cycled LiCoO2 electrodes were discharged to 3.5 V vs. Li and washed with dimethyl carbonate to remove residual salts. Samples were prepared under an argon atmosphere.
[0124] Numerical calculations
[0125] Solvent ionization potentials and electron affinities were calculated by ab initio molecular orbital theory using Gaussian 09W for isolated molecules in the gas phase. Solvent structures were first geometrically optimized in the ground state at the B3LYP / 6-31+g(d,p) level of theory. Ionization potentials and electron affinities were calculated from the difference in electronic energy between the ground state and radical solvent molecules using identical ground state geometries with vertical electronic transitions (Franck-Condon principle). Solvent electrostatic maps were visualized with GaussView.
[0126] XPS analysis
[0127] The XPS spectrum of the lithium foil soaked in fluoromethane for 3 days is shown in Figure 12A. Figure 12A shows lithium metal after soaking in fluoromethane for 3 days. No cleaning of the lithium electrode was performed before XPS analysis. The two peaks at 54.1 eV and 55.5 eV in the Li 1s spectrum correspond to CH3Li and LiF, respectively, which are consistent with the XRD and FTIR data shown in Figures 19 and 20, respectively. In the C 1s spectrum, the peak at 283.4 eV assigned to CH3Li (57) and the broad CF peak at 288 eV are probably derived from the reduction of fluoromethane by proton absorption, leaving the CF bond intact. The small CO peak at 286.3 eV and the peak at 531.3 eV in the O 1s spectrum must arise from oxygen impurities in both the lithium metal and the fluoromethane solvent, since no other oxygen source is present. The LiF (684.6 eV) and CF (686.7 eV) peaks in the F 1s spectrum match the Li 1s and C 1s spectra. The analysis obtained supports the theory that fluoromethane decomposes at the lithium metal surface, with LiF and CH3Li being the main products. However, the layer created on the lithium surface is not compact or electrically insulating enough to prevent further reduction of the solvent, and the lithium metal is completely decomposed.
[0128] Carbon dioxide is reduced at the lithium surface, producing a thin, electrically insulating Li2CO3 layer, as evidenced by both the Li 1s (54.5 eV) and C 1s (289.5 eV) spectra. The LiF peaks at 55.5 eV and 684.7 eV in the Li 1s and F 1s spectra, respectively, indicate that fluoromethane is still reduced at the lithium surface, even when CO2 is added. However, methyllithium is not present in the bulk SEI, as CO2 likely reacts with CH3Li to produce CH3CO2Li, which can further decompose into other compounds (which may further contribute to the CO peaks at 286.3 eV and 533.4 eV). The resulting SEI is composed of LiF and Li2CO3, and acts as a suitable passivation layer to prevent further chemical reduction of the electrolyte system.
[0129] The surface of the lithium metal counter electrode used in the plating and stripping experiments was analyzed by XPS after 400 cycles, and the data are shown in Figure 12C. Figure 12C shows the surface of the lithium metal counter electrode after 400 cycles in 0.2 M LiTFSI in FM:CO2 19:1. The lithium electrode was not cleaned prior to XPS analysis. All peaks seen on the uncycled lithium cell surface in Fig. 12B are also present on the cycled lithium metal surface, except for the CO peak at 533.4 eV, which is likely due to the slow rate of CH3Li decomposition during cycling. Fig. 12B shows lithium metal after immersion in FM:CO2 19:1 for 3 days. The lithium electrode was not cleaned prior to XPS analysis. In the C 1s spectrum, an additional peak is seen at 292.0 eV due to C-F3 bonds, which may correspond to traces of LiTFSI salt on the SEI surface or reduced TFSI. -ions, which corresponds to the CHF3 from the cations. Further comparison of the cycled and uncycled spectra reveals a clear increase in Li2CO3 relative to the other components, making up the majority of the SEI. This indicates that the reduction of carbon dioxide, even at 5 wt%, is favorable for the reduction of fluoromethane during electrode cycling, which is probably the main reason for the high and stable plating and stripping efficiencies observed with these novel electrolytes.
[0130] 12D and 12E show the results of the conventional electrolyte system (1M in EC:DEC 1:1), respectively. Figures 12D and 12E show typical XPS spectra of lithium metal after immersion in 1M LiPF6 in EC:DEC 1:1 and 1M LiPF6 in EC:DEC 1:1, respectively. Lithium metal after 400 cycles in LiPF6. No cleaning of the lithium electrode was performed prior to the XPS analysis. Lithium metal electrodes treated with many conventional liquid electrolytes and salts have been comprehensively observed by many groups, especially by D. Aurbach's group. From previous studies, it is known that both EC and DEC are reduced to ROCO2Li species and small amounts of ROLi at the lithium surface. Furthermore, LiF will be produced by the decomposition of LiPF6. Our XPS results are in good agreement with these results. In the 1s spectrum of C, the peaks at 284.6, 286.3, 288.2, and 289.9 eV correspond to hydrocarbon, CO, OCO, and -OCO2Li species, respectively. In the case of LiF, both 55.5 eV and 684.7 eV peaks appear in the spectrum. The peaks at 53.5 eV and 527.8 eV also reflect the generation of ROLi, which may be the decomposition product of the large RORO2Li-type polymer. The broad peak at 687.0 eV is assigned to FPs from LiPF6 decomposition. After 400 cycles, the ROLi peaks at 53.5 eV and 527.8 eV disappeared, and the peaks related to ROCO2Li became more intense. The peak at 533.3 eV became larger after cycling, corresponding to the generation of more CO-bonded species in the SEI phase. In addition, the proportion of FP species also increased, suggesting that both the electrolyte and LiPF6 salt continuously decompose at the interface during cycling.
[0131] To investigate the SEI layer created at higher potentials, XPS was also performed on the LiCoO2 electrode before and after five cycles at C / 10 rate, +25° (discharged to 3.5 V vs. Li before analysis). Figure 13A shows the XPS spectrum of the LiCoO2 electrode before cycling. Figure 13B shows the electrode before and after five cycles from 3.5 to 4.1 V. The Co 2p shows a clearly differentiated profile, with 2p3 / 2 and 2p1 / 2 components at 780.3 and 795.1 eV. The satellite peak is located at 10 eV higher binding energy than the main peak, as expected. The peaks at 54.3 and 529.6 eV in the Li 1s and O 1s spectra correspond to bulk LiCoO2, respectively. The broad peak at 531.6 eV in the O 1s spectrum arises from both organic species and surface defects in LiCoO2 and has defect coordinates. The peaks at 290.7 eV and 688.0 eV in the Li 1s and F 1s spectra, respectively, are assigned to the C-F2 bonds present in the PVDF binder. These peak positions correspond well with previously reported data.
[0132] After five cycles in liquefied gas electrolyte (0.2M LiTFSI in FM:CO2 19:1), there was only a slight change from the pre-cycle spectrum shown in FIG. 13B, which shows LiCoO2 cycled five times with 0.2M LiTFSI in FM:CO2 19:1. Small peaks are present in the Li 1s, C 1s, and O 1s spectra corresponding to residual salts that were not removed during the dimethyl carbonate wash. Since carbon dioxide is expected to be stable at the potentials seen at this electrode surface and no other oxygen sources are present, the increase in peaks seen in the O 1s spectrum is likely due to changes in the surface oxygen of the LiCoO2 electrode and is not related to the formation of an additional surface layer on the electrode. No other major changes were seen in the XPS spectra, indicating that very little, if any, SEI layer forms at the cathode surface in the fluoromethane-derived electrolyte system.
[0133] In contrast to the fluoromethane-based electrolyte, after five cycles in a conventional liquid electrolyte (1M LiPF6 in EC:DEC 1:1), there is a considerable change in the F 1s and O 1s XPS spectra shown in FIG. 13C. FIG. 13C shows LiCoO2 cycled five times with 1M LiPF6 in EC:DEC 1:1. The XPS spectra in FIGS. 13B and 13C were obtained in the lithiated state at 3.5 V vs. Li after washing with dimethyl carbonate. The new peak at 685.2 eV is characteristic of LiF, which is also demonstrated by the appearance of a peak characteristic of LiF at 56.3 eV in the Li 1s spectrum. The LiF component is generally associated with the PF6 at the cathode surface. - It is cited as a decomposition product of the anion. In addition, fluorophosphate intermediates (i.e. Li x PF y O z There are many peaks appearing in the O 1s spectrum, including the peak at 534.7 eV that is assigned to oxygen atoms in the LiCoO2 cathode. The decomposition of the electrolyte at the LiCoO2 cathode surface and the resulting SEI are largely responsible for the increase in the impedance of the cathode, especially at low temperatures.
[0134] Safety and Environmental Aspects
[0135] Hydrofluorocarbons are commonly used in the refrigerant and microelectronics industries. It is important to note the associated safety and environmental concerns, as the use of these solvents in electrolytes for energy storage devices is uncommon. Being highly volatile, poorly soluble in water, and relatively chemically stable, hydrofluorocarbon solvents themselves are generally non-toxic. However, their combustion or decomposition products may contain hydrogen fluoride, which can be highly toxic to humans. Throughout the scope of this study, caution was exercised and no combustion events occurred. However, there was one event in which hydrogen fluoride was released from the chemical decomposition of liquid 2-fluoropropane at relatively high temperatures (indicated by a solution inside a damaged glass conductivity measurement electrode), after which the use of this solvent was discontinued. Hydrofluorocarbon solvents were tested from non-flammable to highly flammable, and from low to high global warming potential. In general, more highly / lowly fluorinated compounds will exhibit lower / higher flammability and higher / lower global warming potential. The global warming potentials of the hydrofluorocarbons tested are shown in Table 4.
[0136] Table 4 shows the global warming potential (GWP) of selected liquefied gas solvents tested (69). [Table 4]
[0137] In some embodiments, the solvents were stored in a recovery tank after use to limit release to the atmosphere. If these solvents are used on a large scale in energy storage devices, a properly sealed cell should prevent release of the solvent to the atmosphere, and proper end-of-life recycling should be incorporated. A more thorough review of the safety and environmental concerns associated with hydrofluorocarbons is provided elsewhere. Throughout the scope of this testing, high-pressure stainless steel cells and tubing were used at rate pressures significantly higher than the highest vapor pressure of the solvent. Although the vapor pressure of the solvent itself is moderate, significant pressures may be observed at higher temperatures if the thermal expansion of the solvent is limited, and attention should be paid to these events.
[0138] Although this patent document contains many specific examples, these should not be construed as limitations on the scope of any invention or the scope that may be claimed, but rather as descriptions of features that may be specific to certain embodiments of a particular invention. Certain features that are described in a patent document in terms of separate embodiments may also be implemented in combination in one embodiment. Conversely, various features that are described in terms of one embodiment may also be implemented in multiple embodiments separately or in any suitable subcombination. Furthermore, although features may be described above as acting in a particular combination and may even be initially claimed, one or more features from a claimed combination may, in some cases, be implemented from that combination, and the claimed combination may relate to a subcombination or a variation of a subcombination.
[0139] Similarly, although operations are shown in a particular order in the figures, this should not be understood as requiring that such operations be performed in the particular order shown, or in sequential order, to achieve desired results, nor should it be understood that all of the shown operations need to be performed.Furthermore, the separation of various system components in the embodiments described in this patent document should not be understood as requiring such separation in all embodiments.
[0140] Only a few implementations and examples have been described; other implementations, improvements and variations may be made based on what is described and shown in this patent document.
[0141] According to a preferred embodiment of the present invention, for example, the following is provided: (Section 1) 1. An electrochemical device comprising: an ionically conductive electrolyte comprising a solution of one or more salts and one or more compressed gas solvents, each compressed gas solvent being in one of a liquid-only phase and a combination of gas and liquid phases, the one or more compressed gas solvent solutions having a vapor pressure greater than atmospheric pressure at room temperature; a housing configured to encase the ionically conductive electrolyte and to provide a pressurized state for the solution of the one or more salts and one or more compressed gas solvents; and a pair of electrodes in contact with the ionically conductive electrolyte. (Section 2) 2. The electrochemical device according to item 1, wherein the compressed gas solvent comprises one or more of fluoromethane, difluoromethane, fluoroethane, difluoromethane, chloromethane, chloroethane, carbon dioxide, tetrafluoroethane, difluoroethane and difluorochloromethane. (Section 3) Item 2. The electrochemical device according to item 1, wherein the one or more salts include one or more of lithium bis(trifluoromethanesulfonyl)imide, lithium hexafluorophosphate, lithium perchlorate, lithium tetrachloroaluminate, lithium tetragallium aluminate, lithium bis(fluorosulfonyl)imide, lithium aluminum fluoride, lithium hexafluoroarsenate, lithium chloroaluminate, lithium chlorotitanate, lithium hexafluorotitanate, lithium tetrabromoaluminate, lithium tetrachloroborate, lithium tetrafluoroborate, lithium tetrachloroaluminate, sodium hexafluorophosphate, and magnesium hexafluorophosphate. (Section 4) Item 1. The electrochemical device according to item 1, further comprising a further gaseous electrolyte containing one or more of sulfur dioxide, carbon disulfide, oxygen, nitrogen and ammonia. (Section 5) Item 3. The electrochemical device according to item 1, wherein at least one of the pair of electrodes is composed of any one of lithium, sodium, magnesium, potassium, sulfur, and oxygen. (Section 6) 1. An electrochemical device comprising: an ionically conductive catholyte comprising a solution of one or more salts and one or more compressed gas catholytes, each compressed gas catholyte being in one of a liquid-only phase and a combination of gas and liquid phases, the one or more compressed gas catholyte solutions having a vapor pressure greater than atmospheric pressure at room temperature; a housing configured to encase the ionically conductive catholyte and to provide a pressurized state for the solution of one or more salts and one or more compressed gas catholytes; an anode electrode in contact with the ionically conductive catholyte and a cathode current collector; An electrochemical device comprising: (Section 7) 7. The electrochemical device according to item 6, wherein the compressed gas catholyte comprises one or more of thionyl fluoride, thionyl fluoride chloride, phosphoryl fluoride, phosphoryl fluoride chloride, sulfuryl fluoride and sulfuryl fluoride chloride. (Section 8) 7. The electrochemical device according to item 6, wherein the one or more salts include one or more of lithium bis(trifluoromethanesulfonyl)imide, lithium hexafluorophosphate, lithium perchlorate, lithium tetrachloroaluminate, lithium tetragallium aluminate, lithium bis(fluorosulfonyl)imide, lithium aluminum fluoride, lithium hexafluoroarsenate, lithium chloroaluminate, lithium chlorotitanate, lithium hexafluorotitanate, lithium tetrabromoaluminate, lithium tetrachloroborate, lithium tetrafluoroborate, lithium tetrachloroaluminate, sodium hexafluorophosphate, and magnesium hexafluorophosphate. (Section 9) 7. The electrochemical device according to item 6, further comprising an additive comprising one or more of lithium chloride, lithium fluoride, sodium fluoride, sodium chloride, bromine monochloride, bromine monofluoride, chloride and fluoride. (Section 10) 7. The electrochemical device according to item 6, wherein the anode is made of one or more of lithium, sodium, calcium, magnesium, aluminum, iron, zinc, cadmium, and lead. (Section 11) 7. The electrochemical device according to item 6, wherein the cathode current collector is made of one or more of activated carbon, carbon black, and carbon nanotubes. (Section 12) 1. A method of making a liquefied gas electrolyte solution, the method comprising: loading a predetermined weight of salt into a cell, wherein said predetermined weight of salt depends on the concentration of said salt and the volume of compressed gas solvent; cooling the cell to a first temperature that is lower than a second temperature of the source of compressed gas solvent; evaporating a controlled amount of the compressed gas solvent from the source and condensing the compressed gas solvent within the cell; and sealing the cell. (Section 13) 13. The method according to claim 12, wherein the condensing operation is carried out using one of a mass flow controller and a mass flow meter via a tube connected to the cell. (Section 14) 13. The method according to claim 12, wherein the sealing operation is performed using any one of a valve, a plug or a welded cover.
Claims
1. 1. An ionically conductive electrolyte comprising a mixture of one or more salts and a solution of one or more liquefied gas solvents, wherein the liquefied gas solvent comprises at least a first component having a vapor pressure greater than 1.01325 bar at a room temperature of 20° C., and wherein the first component is selected from the group consisting of thionyl fluoride, thionyl fluoride chloride, phosphoryl fluoride, phosphoryl fluoride chloride, sulfuryl fluoride, and sulfuryl fluoride chloride, wherein the ionically conductive electrolyte forms a liquid electrolyte.
2. 2. The ionically conductive electrolyte of claim 1, wherein the liquefied gas solvent comprises one or more chemicals selected from the group consisting of fluoromethane, difluoromethane, fluoroethane, chloromethane, chloroethane, ammonia, oxygen, nitrogen, tetrafluoroethane, and difluorochloromethane.
3. 2. The ionically conductive electrolyte of claim 1, wherein the one or more salts comprise one or more of lithium bis(trifluoromethanesulfonyl)imide, lithium hexafluorophosphate, lithium perchlorate, lithium tetrachloroaluminate, lithium tetragalliumaluminate, lithium bis(fluorosulfonyl)imide, lithium aluminum fluoride, lithium hexafluoroarsenate, lithium chloroaluminate, lithium chlorotitanate, lithium hexafluorotitanate, lithium tetrabromoaluminate, lithium tetrachloroborate, lithium tetrafluoroborate, lithium tetrachloroaluminate, sodium hexafluorophosphate, and magnesium hexafluorophosphate.
4. 10. The ionically conductive electrolyte of claim 1 further comprising an additive comprising one or more of lithium chloride, lithium fluoride, sodium fluoride, sodium chloride, bromine monochloride, bromine monofluoride, chloride and fluoride.
Citation Information
Patent Citations
Lithium battery
CN105591159A
JP1973076030A
Nonaqueous electrochemical cell
JP1984175571A
Secondary battery using lithium
JP1996321300A
High-temperature lithium oxy halide electrochemistry cell
JP2001118584A